MEMBANGUN PENDIDIKAN KARAKTER ANAK MENGGUNAKAN PEMBELAJARAN SASTRA - M As’ad Nahdly (MIYAH : Jurnal Studi Islam, 2020)
Abstract: Literature learning with its relation to character learning plays a significant role. This is because literature essentially includes various values of life and life related to the formation of children's character. Literature in children's education plays a role in developing language, developing cognitive, affective, psychomotor, developing personality, and developing social personalities. Literature as a learning medium can be used receptively (accepting) and expressiveness (ability to express) in character education. Good literary work and contains values that guide students to become good people. Its application in learning, namely the teacher directs students to be able to find positive values from the literature that is read, then applies them in everyday life. Students can learn related to aspects of character, character and behavior, polite speech, and examples of life that must be passed with strong character.Keywords: literature, character, character education